Diseño de un centro de capacitación, comercialización y desarrollo agrícola, para la zona de Azama del cantón Otavalo - Ipiales Arellano, Walter Jesús (2023)
The present Degree work analyzes the agricultural situation of the marginal urban sector of the Azama area in the Otavalo Canton. The Azama area has six sworn communities and an association which are named: Libertad de Azama, Patalanga, Uyancha, Esperanza de Azama, Pigulca, Gualapuro and the Jacinto Collahuazo Association. The entire sector has agriculture and, to a lesser extent, livestock. The formal and functional proposal stems from the principles and elements of the sector which are, the community, culture and agriculture. These aspects related to an important role within the region, that presence of elements is intended to provide the user with comfort, feel relaxed and related to the archi tectural equipment that will be implemented. Through an equipment focused on production, training, innovation and development for agricultural opti mization of the sector, it is intended to route and potentialize crops in the area, being also a reference for the entire province of Imbabura, for this purpose it has been proposed to propose different functional spaces such as a training center, auditoriums, administrative area, workshops, farms, cafeteria, product marketing spaces, wineries, which are linked to the agricultural field.